1969
DOI: 10.1111/j.1399-3054.1969.tb09123.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Aliphatic Aldehydes and Related Compounds on the Growth of Dipodascus aggregatus

Abstract: The growth of Dipodascus aggregatus in cultures inoculated with cells from the acceleration phase of growth was stimulated by the saturated and unbranched aliphatic C(3) C(4) , and C(6) to C(11) aldehydes (80 μM]. Nonanal was most active in stimulating growth. The C(12) aldehyde inhibited growth. The C(5) , aldehyde generally inhibited growth. - Nonan did not affect growth. 2-Nonanone and 5-nonanone promoted growth insignificantly. - In cultures inoculated with cells from the exponential phase growth was unaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Accumulating evidence suggests that they may also be important for plant defense. Several in vitro studies have shown that volatile aldehydes and alcohols inhibit the growth of fungal species as determined by measurement of hyphal growth, dry matter accumulation, and/or germination of spores (Major et al, 1960;Nyman, 1969;Nandi, 1977; Urbasch, 1984; Gueldner et al, 1985; Zeringue and McCormick, 1989;Hamilton-Kemp et al, 1992). We have shown that these compounds produced by crushed foliage inhibited pollen germination (Hamilton-Kemp et al, 1991).…”
Section: Introductionmentioning
confidence: 73%
“…Accumulating evidence suggests that they may also be important for plant defense. Several in vitro studies have shown that volatile aldehydes and alcohols inhibit the growth of fungal species as determined by measurement of hyphal growth, dry matter accumulation, and/or germination of spores (Major et al, 1960;Nyman, 1969;Nandi, 1977; Urbasch, 1984; Gueldner et al, 1985; Zeringue and McCormick, 1989;Hamilton-Kemp et al, 1992). We have shown that these compounds produced by crushed foliage inhibited pollen germination (Hamilton-Kemp et al, 1991).…”
Section: Introductionmentioning
confidence: 73%
“…Estudio de la composición del hongo Lentinula edodes usando herramientas ómicas y su potencial en la producción de un alimento funcional uniéndose a grupos amino libres presentes en la cadena polipeptídica de estas. (257).…”
Section: ▪ Aldehído Grasounclassified
“…As could be expected, tbey are present among tbe volatiles from the heat-dried pine wood-chips (FLODIN and ANDERSSON 1977). Some cases are also known where these aldehydes increase the growth rate (FRIES 1960, 1961, NYMAN 1969 and alter the morphology of fungi (NoRRMAN 1968, FRIES 1975. FRIES (1975) has also shown that hexanal is an active substance in inducing coremia formation in Ceratocystispiceae.…”
Section: Discussionmentioning
confidence: 85%